2013
DOI: 10.4046/trd.2013.74.5.215
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Distribution of Nontuberculous Mycobacteria from 2005 to 2011 in Cheonan, Korea

Abstract: BackgroundNontuberculous mycobacteria (NTM) are considered opportunistic pathogens, and several species of NTM are associated with human diseases that typically involve the pulmonary, skin/soft tissue, or lymphatic systems; such infection may also cause disseminated diseases. Recent studies have reported increasing rates of NTM-induced disease worldwide.MethodsRespiratory samples are being analyzed for acid-fast bacilli (AFB) culture and NTM identification at Dankook University Hospital in Cheonan, Korea, from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 30 publications
4
7
0
Order By: Relevance
“…This is in line with previous studies from Korea (457812). M. abscessus-massiliense complex is the second most common etiologic organism in pulmonary NTM disease in Korea (12).…”
supporting
confidence: 93%
“…This is in line with previous studies from Korea (457812). M. abscessus-massiliense complex is the second most common etiologic organism in pulmonary NTM disease in Korea (12).…”
supporting
confidence: 93%
“…avium complex was the most common NTM and M . intracellulare accounted for 51.3% of all specimens [ 23 ]. Other research conducted in east Asia showed that M .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that there is great geographic diversity in the distribution of NTM species ( 1 , 2 , 4 , 5 ). However, few studies have investigated the distribution of NTM species, including colonizers and causative pathogens, with respect to patient gender and age ( 6 , 7 ). …”
mentioning
confidence: 99%